2020
DOI: 10.1080/10790268.2019.1708600
|View full text |Cite
|
Sign up to set email alerts
|

Hemostatic parameters in patients with spinal cord injury in subacute and chronic phase of the rehabilitation

Abstract: Objective: The goal of this study was to measure hemostatic markers after SCI. Design: Assesing changes in coagulation and fibrynilitic system in SCI patients in different time post injury to Cross-sectional study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…This may indicate that DVT in group II of patients (3 to 6 months after SCI) developed in the acute period post-injury but was not diagnosed earlier because ultrasound screening was not done and DVT was not fully symptomatic. Our present findings are consistent with our previous study which showed that the level of D-dimer remained high in patients up to 3 months after SCI, with the median of 2540 ng/mL and average value of 4488 ng/mL [ 30 ]. Matsumoto et al [ 5 ] observed very high average D-dimer values of 14,600 ng/mL among patients several days after SCI, which did not differ significantly between groups with and without DVT.…”
Section: Discussionsupporting
confidence: 93%
“…This may indicate that DVT in group II of patients (3 to 6 months after SCI) developed in the acute period post-injury but was not diagnosed earlier because ultrasound screening was not done and DVT was not fully symptomatic. Our present findings are consistent with our previous study which showed that the level of D-dimer remained high in patients up to 3 months after SCI, with the median of 2540 ng/mL and average value of 4488 ng/mL [ 30 ]. Matsumoto et al [ 5 ] observed very high average D-dimer values of 14,600 ng/mL among patients several days after SCI, which did not differ significantly between groups with and without DVT.…”
Section: Discussionsupporting
confidence: 93%
“…Several patients with SCI were observed to have DVT by Doppler angiography during rehabilitation [ 32 ]. Notably, for sub-acute and even chronic patients with SCI had disturbed coagulation and fibrynolitic system, regardless of whether VTE was formed or not [ 33 ]. Research indicates D-dimer levels in SCI adults were markedly 70% higher in adults with SCI compared with non-injured adults [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The coagulation-brinolytic axis plays a central role in atherosclerosis and thrombotic events (8)(9)(10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Increased activity of the coagulation system and enhanced brin deposition if not counteracted with brinolysis and the degradation of brin deposit at sites of vascular injury or on atheromatous plaques precipitate vascular events (13). Indeed, coagulation and brinolytic dysfunction underlie ischemic stroke and MI (8)(9)(10)(11)(12)(13)(14)(15). Activation of coagulation cascade factors VII, VIII, and X amplify thrombin generation, brin deposition, and are independently associated with atherosclerotic disease and major vascular events later in life in the general population (12,13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation